Who are you? : the kid's guide to gender identity - Pessin-Whedbee, Brook; Bardoff, Naomi (London : Jessica Kingsley Publishers, 2017)
Presents clear and direct language for understanding and talking about how we experience gender: our bodies, our expression and our identity.
Includes a guide for adults.
May include an interactive wheel.
2.8
K-3
Diversity collection. Purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Gender identity -- Juvenile literature; Transsexualism -- Juvenile literature; Sex role -- Juvenile literature; Gender identity; Transsexualism; Sex role; Gender role; Transsexualism; Gender role